Feasibility of an Objective Approach Using Acoustic Change Complex for Evaluating Spectral Resolution in Individuals with Normal Hearing and Hearing Loss - Kang, Soojin; Woo, Jihwan; Lee, Kyung Myun; Seol, Hye Yoon; Hong, Sung Hwa; Moon, Il Joon (Journal of integrative neuroscience, 2025)
Background: Identifying the temporal and spectral information in sound is important for understanding speech; indeed, a person who has good spectral resolution usually shows good speech recognition performance. The spectral ripple discrimination (SRD) test is often used to behaviorally determine spectral resolution capacity. However, although the SRD test is useful, it is difficult to apply to populations who cannot execute the behavioral task, such as younger children and people with disabilities. In this study, an objective approach using spectral ripple (SR) stimuli to evoke the acoustic change complex (ACC) response was investigated to determine whether it could objectively evaluate the spectral resolution ability of subjects with normal hearing (NH) and those with hearing loss (HL). Method: Ten subjects with NH and eight with HL were enrolled in this study. All subjects completed the behavioral SRD test and the objective SR-ACC test. Additionally, the HL subjects completed speech perception performance tests while wearing hearing aids. Results: In the SRD test, the average thresholds were 6.48 and 1.52 ripples per octave (RPO) for the NH and HL groups, respectively, while in the SR-ACC test, they were 4.90 and 1.35 RPO, respectively. There was a significant difference in the average thresholds between the two groups for the SRD (p < 0.001) and the SR-ACC (p < 0.001) tests. A significant positive correlation was observed between the SRD and SR-ACC tests (ρ = 0.829, p < 0.001). In the HL group, there was a statistically significant relationship between speech recognition performance in noisy conditions and the SR-ACC threshold (ρ = 0.911, p < 0.001 in Sentence score of Korean Speech Audiometry (KSA)). Conclusions: The results supported the feasibility of the SR-ACC test to objectively evaluate auditory spectral resolution in individuals with HL. This test has potential for use in individuals with HL who are unable to complete the behavioral task associated with the SRD test; therefore, it is proposed as a more inclusive alternative to the SRD test.